Analisis Peran Media dalam Isu Perselingkuhan Selebgram dalam Membentuk Opini Publik - Zalfa Labani Fasha; Argita Zahra Syah; Allessandra Ranindhita Caropeboka (STISIPOL Raja Haji, 2025)
In this research analysis, it analyzes the role of the media in shaping public opinion regarding the issue of infidelity between celebrities. In this research, we take the issue of infidelity that previously occurred between celebrities Azizah Salsha and Salim Nauderer. This study aims to explore the impact of news coverage on public opinion. Using agenda-setting and framing theories, this study examines how media outlets present issues, influencing societal perspectives and public morality. The methodology combines content analysis of news reports and thematic analysis of in-depth interviews with selected respondents. Results highlight the significant role of the media in shaping perceptions and polarizing public opinions on sensitive issues. The existing news tends to be sensationalized so that public stereotypes become strong, influencing, and social media users who follow the news about celebgrams also influence the developing narrative.